Rapid endothermal development of juvenile pacific bluefin tuna - Kitagawa, Takashi; Abe, Takaaki K.; Kubo, Keitaro; Fujioka, Ko; Fukuda, Hiromu; Tanaka, Yosuke (Frontiers in Physiology, 2022)
Pacific bluefin tuna (PBT) is a commercially important species in the fishing industry as it has excellent meat quality and high economic value. However, in 2020, the estimated adult fish stock was only 6.4% of the initial stock, although the stock numbers are gradually increasing. As a result, concerns about long-term scarcity have increased. An important trait of PBT is their ability to maintain their body temperature above the ambient temperature, which allows them to occupy a wider ecological niche. However, the size at which this ability develops is unclear. Therefore, this study aimed to clarify this point by monitoring the body temperature and the surrounding ambient temperature as the fish grew. Pacific bluefin tuna with fork lengths (FLs) ranging from 19.5 to 28.0 cm were implanted with electronic devices (archival tags) and released into the ocean. Data from 41 fish were obtained (recorded body and water temperatures, light level, and swimming depth (pressure) at 30-second intervals) and analyzed to elucidate the development of the ability of PBT to maintain a high body temperature. It was found that the body temperature of a PBT (< FL of ca. 40 cm) decreased in response to a vertical movement down to cooler depths, but higher body temperatures were maintained as the fish grew. The body temperature was then continuously maintained above ambient temperatures and fluctuated independently when fish attained more than around 40 cm FL. Estimation of the whole-body heat-transfer coefficient and heat-production rate indicated that the latter decreased slowly with the growth of the animals, while the former decreased by one order of magnitude when the animals reached an FL of 52 cm. Additionally, in the daytime, the whole-body heat-transfer coefficient was significantly higher than that at nighttime. Unlike other fishes, including other Thunnus species, inhabiting tropical/subtropical waters, it was found that PBT rapidly acquire higher thermo-conservation ability when young, suggesting that the trait is the result of an adaptation allowing the fish to capture the high-quality prey abundant in temperate waters to achieve a high growth rate during the yearling period.